Stable pH Suppresses Defense Signaling and is the Key to Enhance Agrobacterium-Mediated Transient Expression in Arabidopsis Seedlings. Issue 1 (December 2018) - Wang, Yi-Chieh; Yu, Manda; Shih, Po-Yuan; Wu, Hung-Yi; Lai, Erh-Min
Abstract Agrobacterium -mediated transient expression is a powerful analysis platform for diverse plant gene functional studies, but the mechanisms regulating the expression or transformation levels are poorly studied. Previously, we developed a highly efficient and robustAgrobacterium -mediated transient expression system, named AGROBEST, forArabidopsis seedlings. In this study, we found that AGROBEST could promote the growth of agrobacteria as well as inhibit the host immunity response. When the factor of agrobacterial growth is minimized, maintaining pH at 5.5 with MES buffer was the key to achieving optimal transient expression efficiency. The expression of plant immunity marker genes, FRK1 andNHL10, was suppressed in the pH-buffered medium as compared with non-buffered conditions in Col-0 and anefr-1 mutant lacking the immunity receptor EFR recognizing EF-Tu, a potent pathogen- or microbe-associated molecular pattern (PAMP or MAMP) ofA .tumefaciens . Notably, such immune suppression could also occur inArabidopsis seedlings withoutAgrobacterium infection. Furthermore, the PAMP-triggered influx of calcium ions was compromised in the pH-buffered medium. We propose that the enhanced transient expression efficiency by stable pH was due to inhibiting calcium ion uptake and subsequently led to suppressing immunity againstAgrobacterium .